Lucy's Law comes into force. (2nd April 2020) - Abraham, Marc
Abstract : After years of campaigning Lucy's Law was passed in the summer of 2019, and became enforceable from April 6th this year. It ensures that puppies and kittens can only be sold in the place in which they were born, and in the presence of their mother.